PROSES PERIZINAN TERHADAP USAHA CAFE DI KOTA PEKANBARU TAHUN 2022-2023 - Putra, Riski Febriandi; ', Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
At this time in the city of Pekanbaru, there have been many scattered café businesses that are used as one of the places to visit the community to relax and socialize. So not a few entrepreneurs are interested in establishing a café business. Efforts that must be considered and understood first by business actors are to take care of the café business license they have in order to obtain a permit from the local government. To take care of the permit, there are processes or stages that have been implemented by the government as stated in the Regulation of the Mayor of Pekanbaru Number 78 of 2022 concerning the Implementation of Business Licensing in the City of Pekanbaru. In the regulation, it is explained that the management of low-risk business licenses, in this case the café business, the licensing is carried out online by preparing several documents in the form of KTP, BPJS, NPWP and email through the OSS Institution to get a Business Identification Number (NIB) as a sign that the business can run. This research is a descriptive research with a qualitative approach, the types of data used are primary data and secondary data, primary data is obtained directly from sources, with secondary data, namely supporting data to strengthen primary data. Data collection techniques are carried out by means of interviews and documentation. The results of this study show that the governance of café business licensing in Pekanbaru City has run optimally because all licensing processes managed by DPMTPSP run in a transparent and systematic manner by DPMPTSP, but it is necessary to increase socialization related to café business licensing to café business actors in Pekanbaru City because there are still many café business actors who do not have a business license and do not obey the rules or do not prioritize regulations that have already taken place.The inhibiting factors are the lack of public awareness, the level of public concern and compliance with existing laws and the level of the community's economy. Keywords: Process, licensing, cafe business